The Kāffah of Islamic Scale: Development and Validation - Ilmi Amalia; Achmad Syahid; Ikhwan Lutfi; Wahyu Saputra (Fakultas Psikologi UIN Syarif Hidayatullah Jakarta, 2023)
Prudent study and analysis of the religiosity instruments that have been circulating it are found that there are many variations of instruments measuring the religiosity of Muslims. This is due to differences in the conceptual constructs used by the researchers as the basis for developing such instruments. The use of concepts and instruments that are not based on Islamic religiosity has the potential to distance the measuring instrument from what psychological behavior to be measured, while the measuring instrument based on Islamic religiosity is also not yet fully solid, in line, and be close to each other with Islam. Dissatisfaction with the instruments based on the constructs and instruments of Islamic religiosity that have been compiled has encouraged researchers to develop religious instruments based on Islamic teachings in a precise and solid manner. This instrument is called the Kāffah of Islamic Scale (KIS). The results of the psychometric test and empirical data show that the Kāffah of Islamic Scale (KIS) has a good factor structure through the testing phase of the unidimensional fit model. The Kāffah of Islamic Scale (KIS) measuring instrument consists of five dimensions, namely belief, formal ritual, interpersonal, personal, and morality. There are 33 valid items to measure the Islamic construct of the kāffah composed of five items representing the belief dimension, six items representing the formal dimension of ritual, thirteen items representing interpersonal relationships, twelve items representing the personal dimension, and three items representing the morality dimension. Overall, the results of this research provide preliminary evidence to support the use of the Kāffah of Islamic of Scale (KIS) as a measurement tool that has conceptual and psychometric strengths.